Islam, politics, anthropology - Osella, Filippo; Soares, Benjamin F. (Wiley-Blackwell, 2010)
Islam, Politics, Anthropology offers critical reflections on past and current studies of Islam and politics in anthropology and charts new analytical approaches to examining Islam in the post-9/11 world.